The Flora Compositions of Nitrogen-Fixing Bacteria and the Differential Expression of nifH Gene in Pennisetum giganteum z.x.lin Roots. (24th April 2021) - Lin, Biaosheng; Liu, Jiamin; Zhang, Xue; Weng, Changren; Lin, Zhanxi
Abstract : The flora compositions of nitrogen-fixing bacteria in roots of Pennisetum giganteum z.x.lin at different growth stages and the expression and copy number of nitrogen-fixing gene nif H were studied by Illumina Miseq second-generation sequencing technology and qRT-PCR. The results showed that there were more than 40, 000 50, 000 effective sequences in 5 samples from the roots of P. giganteum, with Proteobacteria and Cyanobacteria as the dominant nitrogen-fixing bacteria based on the OTU species annotations for each sample and Bradyrhizobium as the core bacterial genera. The relative expression and quantitative change of nif H gene in roots of P. giganteum at different growth stages were consistent with the changes in the flora compositions of nitrogen-fixing microbia. Both revealed a changing trend with an initial increase and a sequential decrease, as well as changing order as jointing stage>maturation stage>tillering stage>seedling stage>dying stage. The relative expression and copy number of nifH gene were different in different growth stages, and the difference among groups basically reached a significant level (p < 0.05 ). The relative expression and copy number of nif H gene at the jointing stage were the highest, and the 2 -△△CT value was 4.43 folds higher than that at the seedling stage, with a copy number of 1.32 × 10 7 /g. While at the dying stage, it was the lowest, and the 2 -△△CT value was 0.67 folds, with a copy number of 0.31 × 10 7 /g.